PENINGKATAN PEMBELAJARAN MENULIS TEKS BERITA DENGAN MENGGUNAKAN MODEL AUDITORY INTELLECTUALLY REPETITION (AIR) PADA SISWA SMP - Ghaniyu, Naftalisa; Kirana, Diana; Sudrajat, Rochmat Tri (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research was in the background because of the lack of students in literacy so that researchers sought to improve the creativity of students in writing news texts. The implementation of news text learning teaches students to understand the news text, so that researchers apply the intellectually repetition (AIR) auditory learning model so that students can listen, understand, and rewrite the learning news text that has been understood. The researcher used an experimental method with a design (one group pre-post-test) and collected data with a technique in the form of a pre-test and post-test final test. The sample used was class VIII students with the number 30. The results of the tests that were carried out obtained differences and enhancements, namely in the pre-test the average value obtained was 61.5% while the post-test that had been given treated using the learning model (AIR) obtained the value is 79.33% and the difference between the pretest and post-test is 17.83%. So this learning of the intellectually repetition (AIR) auditory model can be applied by learning to write news texts and the results obtained in the post-test scores get a significant increase of 17.83%.